Modeling of information-analytical support for the timber industry complex - Poluektov Alexander; Skvortsova Tatiana; Anikeev Evgeny; Yagodkin Alexander (BIO Web of Conferences)
The article describes the methods of designing the information network of the timber industry complex. Algorithms for generating user requests and converting them to a format that is understandable for processing in the system are described. A model of the behaviour of a multi-purpose information system is developed and mathematically justified, and its reachability is checked. The resource allocation problem is also formulated and the solution of the problem is mathematically justified. The possibility of conflicts appearing in the system is studied and evaluated, possible conflicts are identified and a mathematical apparatus for resolving conflicts is developed, as well as subsets of desirable and undesirable behaviour of subsystems are studied. In addition to the theoretical substantiation of the design methodology, the article also contains mathematical tools that can be useful for developing various information networks.